2007
DOI: 10.1002/jemt.20445
|View full text |Cite
|
Sign up to set email alerts
|

Clinical two‐photon microendoscopy

Abstract: Two-photon medical imaging has found its way into dermatology as an excellent method for noninvasive skin cancer detection without need of contrast agents as well as for in situ drug screening of topically-applied cosmetical and pharmaceutical components. There is an increasing demand to apply the multiphoton technology also for deep-tissue skin imaging as well as for intracorporal imaging. We report on the first clinical use of multiphoton endoscopes, in particular of a miniaturized rigid two-photon GRIN lens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 11 publications
2
139
1
Order By: Relevance
“…The ageing skin of young and old people show a significant difference with the semi-quantitative evaluation of dermal collagen and elastin fibre network assessed in vivo by the multiphoton excitation imaging (Koehler et al, 2006). Procedures of selective imaging as well as spectral fluorescence lifetime analysis by means of multiphoton laser tomography support diagnostic decisions and may improve the process of non-invasive early detection of melanoma (König et al, 2007;Dimitrow et al, 2009) (Fig. 9) and non-melanoma skin cancer (Paoli et al, 2008).…”
Section: In Vivo Drug Screening and Administration In Skin And Kidneymentioning
confidence: 99%
“…The ageing skin of young and old people show a significant difference with the semi-quantitative evaluation of dermal collagen and elastin fibre network assessed in vivo by the multiphoton excitation imaging (Koehler et al, 2006). Procedures of selective imaging as well as spectral fluorescence lifetime analysis by means of multiphoton laser tomography support diagnostic decisions and may improve the process of non-invasive early detection of melanoma (König et al, 2007;Dimitrow et al, 2009) (Fig. 9) and non-melanoma skin cancer (Paoli et al, 2008).…”
Section: In Vivo Drug Screening and Administration In Skin And Kidneymentioning
confidence: 99%
“…This limitation may be overcome by technical developments of multi-photon microscopy scanner probes connected to optic fibres, which have recently facilitated in vivo imaging of the mouse central nervous system over extended periods of time [10,11,18]. König et al have further demonstrated that multi-photon microscopy can be performed through optical rods [12]. However, the device used for this study does allow fast optical serial biopsies during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…GRIN rod lens can also be used directly to couple with a microscope objective with similar or matching numerical aperture for microendoscopic imaging. In this case the pitch length of the GRIN lens to be used can be slightly shorter than the integral multiple of ½ pitches [21]. The practical issues of using a single GRIN lens are 1) the physical length of the GRIN lens that can be made useful for deep tissue probing, 2) the diameter of the GRIN lens which is desired to be small for microendoscopic applications and 3) the optical artifacts generated by the GRIN lens (e.g.…”
Section: Laser Scanning Microendoscopy Using Grin Lens Probesmentioning
confidence: 99%
“…GRIN lens is convenient for coupling light into fiber optics due to its cylindrical shape and therefore widely used as a component in telecommunication devices. As a lens, it also finds applications in the areas of optical spectroscopy [10,11] and imaging including optical coherent tomography (OCT) [12,13], endoscopy [14][15][16] and optical microscopy [17][18][19][20][21][22]. GRIN lenses were reported to be implemented in conjunction with both confocal and two-photon fluorescence microscopes for in vivo imaging of the brain [18,19,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation